Optimizing Simulation of the Arm Stroke in Crawl Swimming Considering Muscle Strength Characteristics of Athlete Swimmers - Motomu NAKASHIMA; Shun MAEDA; Takahiro MIWA; Hiroshi ICHIKAWA (Journal of Biomechanical Science and Engineering, 2012)
In this study, the optimal arm strokes in crawl swimming which maximize the swimming speed and propulsive efficiency were solved computationally. For this objective, an optimizing method which consisted of the random search and the PSO (Particle Swarm Optimization) algorithm was constructed. In order to consider the muscle strength characteristics of the swimmer as the constraint condition of the optimization, an experiment to measure the maximum joint torques was carried out for various joint angles and angular speeds. Using the measured experimental data as the reference values, a musculoskeletal simulation model was constructed. By the constructed musculoskeletal model, muscle strength characteristics in various conditions were investigated and used to create a database. Using this database, the optimizing calculation was finally conducted and the following results were obtained: In the optimization maximizing the swimming speed, the swimming speed became maximum when the stroke cycle was 0.9 s. A relatively I-shaped stroke was obtained in this case. In the optimization maximizing the propulsive efficiency, the propulsive efficiency became maximum when the stroke cycle was 1.3 s. A relatively S-shaped stroke was obtained in this case. Two strokes which respectively maximized the swimming speed and propulsive efficiency were very similar to each other when the stroke cycles were the same. The swimming speeds and stroke cycles obtained in the optimizing calculation were within reasonable ranges compared to the actual races.